2016
DOI: 10.1016/j.puhe.2015.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences, family functioning and adolescent health and emotional well-being

Abstract: Objectives Adverse childhood experiences (ACE) have been consistently linked in a strong and graded fashion to a host of health problems in later adulthood but few studies have examined the more proximate effect of ACE on health and emotional well-being in adolescence. Study Design Nationally representative cross-sectional study. Methods Using logistic regression on the 2011/12 National Survey of Children’s Health, we examined the cumulative effect of total ACE score on the health and emotional well-being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
76
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 30 publications
7
76
2
7
Order By: Relevance
“…Since the influential ACE study, researchers have made great advancements in understanding the relationship between ACEs and health outcomes in adults . More recent research has begun exploring how current experiences of ACEs relate to current health challenges among children and youth . However, less is known about which ACEs are most salient in their association with health outcomes in young, vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the influential ACE study, researchers have made great advancements in understanding the relationship between ACEs and health outcomes in adults . More recent research has begun exploring how current experiences of ACEs relate to current health challenges among children and youth . However, less is known about which ACEs are most salient in their association with health outcomes in young, vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] More recent research has begun exploring how current experiences of ACEs relate to current health challenges among children and youth. [11][12][13][14] However, less is known about which ACEs are most salient in their association with health outcomes in young, vulnerable populations. Such information may be helpful for designing service approaches in health care and child welfare that aim to mitigate emerging health concerns.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] Positive individual-, family-, and community-level factors, including high levels of family functioning and parental engagement, are associated with favorable outcomes for children and adolescents who have been exposed to ACEs. [21][22][23] Family functioning in particular is a protective factor against poverty, neighborhood violence, poor parental relationships, and adolescent mental health concerns. [24][25][26] One national study found that resilience, defined as "staying calm and in control when faced with a challenge," lessened the impacts of ACEs on grade repetition and poor school engagement.…”
Section: Prevalence and Impacts Of Aces In Adolescencementioning
confidence: 99%
“…Similar to the adult literature, research on the health and well-being of children also finds this association between adversity and poor health. Children exposed to adversity as compared to children without these exposures are at an increased risk for social disruptions, such as perpetrating violence and being involved in the criminal justice system; 52-56) mental health and behavioral problems, such as depression, anxiety and attention-deficit hyperactivity disorder; 57-66) obesity; [67][68][69][70] asthma; [71][72][73] risk for cardiovascular disease; 70,74) multiple somatic complaints such as headaches, fatigue, gastrointestinal 57,75,76) and perhaps, the most disturbing, is the negative impact on the developmental and intellectual functioning of children. 57,63,67,[77][78][79][80][81] The loss of the potential functional and intellectual capacity of people due to childhood violence exposure is daunting.…”
mentioning
confidence: 99%